2012
DOI: 10.1080/19345747.2012.656182
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Start of the College Pipeline: Ninth-Grade Findings From an Experimental Study of the Impact of the Early College High School Model

Abstract: Early college high schools are a new and rapidly spreading model that merges the high school and college experiences and that is designed to increase the number of students who graduate from high school and enroll and succeed in postsecondary education. This article presents results from a federally funded experimental study of the impact of the early college model on Grade 9 outcomes. Results show that, as compared to control group students, a statistically significant and substantively higher proportion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 21 publications
(20 reference statements)
1
59
0
Order By: Relevance
“…The significant effects of ECHS on both policy implementation and student outcomes are supported by the results of the ongoing experimental study of the impacts of the model on student academic and behavioral outcomes (Edmunds et al, 2010;Edmunds et al, 2012). These studies report that ECHS have a significant impact on student outcomes.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…The significant effects of ECHS on both policy implementation and student outcomes are supported by the results of the ongoing experimental study of the impacts of the model on student academic and behavioral outcomes (Edmunds et al, 2010;Edmunds et al, 2012). These studies report that ECHS have a significant impact on student outcomes.…”
mentioning
confidence: 76%
“…In the 9th and 10th grades, more ECHS than control students successfully completed college preparatory math and science courses, and more ECHS than control students enrolled in college preparatory courses in other core subjects. ECHS students have significantly fewer absences and lower suspension rates, higher continuous enrollment in school through the 10th grade, higher aspirations to attend 4-year college, higher levels of engagement, and more challenging work than students in the comparison group (Edmunds et al, 2010;Edmunds et al, 2012). ECHS students also report higher levels of implementation of specific policies than comparison students, including better relationships with staff, more rigorous and relevant instruction, higher academic expectations, and more academic and social support .…”
mentioning
confidence: 83%
“…Finally, Edmunds et al (2011) found that significantly more ECHS students had taken and passed at least two core college preparatory mathematics courses beyond Algebra I compared to students in control schools, when controlling for schoollevel clustering and other differences between ECHS and control schools. Edmunds et al (2011) also found a higher proportion of minority students, first-generation college-goers, and low-SES students taking Algebra I and at least two mathematics courses beyond Algebra I in ECHS compared to control schools in unadjusted comparisons, although they do not share adjusted differences between ECHS and control schools for subgroups and note that "not all of these differences are statistically significant" (p. 20) when means are adjusted for clustering and preexisting differences.…”
Section: Positive and Neutral Long-term Outcomes Associated With Univmentioning
confidence: 89%
“…Located on campuses of 2-and 4-year colleges, Early College High Schools (ECHSs) serve students who are underrepresented in the college-going population and provide rigorous courses with the goal of ensuring that all students graduate with a high school diploma and 2 years of university transfer credit or an associate's degree (Edmunds et al, 2011). Located on campuses of 2-and 4-year colleges, Early College High Schools (ECHSs) serve students who are underrepresented in the college-going population and provide rigorous courses with the goal of ensuring that all students graduate with a high school diploma and 2 years of university transfer credit or an associate's degree (Edmunds et al, 2011).…”
Section: Talent Development High Schools Ninth Grade Algebra the Talmentioning
confidence: 99%
“…In the early college, all students are expected to take a college preparatory course of study. Our study shows that this has led to more students taking and succeeding in the courses they need for entrance to college (Edmunds et al, 2012). For example, by the time they graduate from high school, 77% of the early college students had successfully completed a college preparatory course of study compared to 68% of the control group.…”
Section: V97 N5 Kappanmagazineorg 41mentioning
confidence: 78%